2017
DOI: 10.1002/adom.201700753
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Silver–Germanium Nanolayer Metamaterial with the Enhanced Nonlinear Response

Abstract: Plasmonic metamaterials and metasurfaces are important for many linear\ud and nonlinear photonic applications. Here, the possibility to control a nanostructured\ud layer spontaneously formed near an interface of a thin silver film is\ud shown, where the interplay between a grain boundary structure and surface\ud segregation of germanium atoms leads to encapsulation of the grains and,\ud as the result, formation of a composite metamaterial near the film surface.\ud This Ag/Ge composite exhibits strong localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
(44 reference statements)
2
15
0
Order By: Relevance
“…The internal structure of the metamaterial composite generally favours the TE‐mode excitation which has a strong electric field component normal to the nanorod surface. These counterintuitive polarization properties are similar to those observed in other metamaterials with strong internal local fields …”
Section: Radiated Sh Spectra From the Metamaterials Slabsupporting
confidence: 87%
“…The internal structure of the metamaterial composite generally favours the TE‐mode excitation which has a strong electric field component normal to the nanorod surface. These counterintuitive polarization properties are similar to those observed in other metamaterials with strong internal local fields …”
Section: Radiated Sh Spectra From the Metamaterials Slabsupporting
confidence: 87%
“…In the case of metallic films, this was studied both experimentally and theoretically . The main features in the spatial distribution of SHG were discussed in terms of the roughness‐assisted SPP generation as well as the LSP hot spots . For metallic nanostructures, it was numerically shown that small deviations from an ideal form due to asymmetry related to limited fabrication capabilities or surface roughness lead to significant changes in the radiated SHG, even if the linear response of the nanostructures is barely modified.…”
Section: Harmonic Generation In Plasmonic Nanostructures: Perturbativmentioning
confidence: 99%
“…For metallic nanostructures, it was numerically shown that small deviations from an ideal form due to asymmetry related to limited fabrication capabilities or surface roughness lead to significant changes in the radiated SHG, even if the linear response of the nanostructures is barely modified. From this point of view, SHG provides a very sensitive tool for the optical characterisation of plasmonic nano‐objects and surfaces …”
Section: Harmonic Generation In Plasmonic Nanostructures: Perturbativmentioning
confidence: 99%
“…Metal nanolayers, as carriers of surface plasmon waves, may be used in plasmonic, biosensor and functional material applications, provided that they exhibit minimal ohmic and scattering losses [1][2][3][4][5][6][7][8]. Since silver and gold have the smallest imaginary part of permittivity within the visible frequency range, they are routinely applied in plasmonic devices.…”
Section: Introductionmentioning
confidence: 99%
“…This approach considerably reduces the scattering losses of silver films, but has one significant drawback-over time, germanium atoms segregate through silver grain boundaries towards the free surface of the metal [19]. This results in the formation of Ge-encapsulated silver grains near the film's surface which gives rise to interesting optical phenomena like additional plasmonic absorption or strong Second Harmonic Generation (SHG) enhancement [7]. Additionally, this effect substantially increases ohmic losses of the silver films, ultimately excluding such layers from many potential applications [18,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%